An Analysis of an Autoclitic Analogue in Pigeons - Kuroda, Toshikazu (Anal Verbal Behav, 2014)
Using a conditional discrimination procedure, pigeons were exposed to a nonverbal analogue of qualifying autoclitics such as definitely and maybe. It has been suggested that these autoclitics are similar to tacts except that they are under the control of private discriminative stimuli. Instead of the conventional assumption of privacy, which precludes direct manipulation of the controlling variable, the autoclitic was here identified as a response that is jointly determined by its function as a modifier for the consequence of the tact and by some variable that modifies stimulus control of the tact. Following this modified conceptualization, a novel conditional discrimination procedure was developed as an analogue for establishing autoclitic-like behavior in pigeons. Under some conditions, autoclitic-like behavior was established. Methodological challenges in developing an autoclitic analogue in nonhumans are discussed, followed by a consideration of the implications of such analogues for the understanding of verbal and, more broadly, human behavior.